Subcutaneous metastases from rectal carcinoma: A case report - Jasman JW; Mayuha RS; Imtiaz H; Sagap I (Department of Surgery, UKM Medical Centre, 2011)
Subcutaneous metastasis of rectal adenocarcinoma is an infrequent event as it occurs in less than 4% of all patients with rectal malignancy. When present, it signifies an advanced disease and carries poor prognosis. We hereby, present the case of a 51-year-old woman with subcutaneous lesion that turned out to be rectal adenocarcinoma metastases. She was then managed as an advanced case.